Comparative Study of Manual and Software-Aided Rotary Intersection Design Using AutoCAD Civil 3D - Usendi, Ketan Kumar; Birali, R. R. L.; Singh, Akhand Pratap (International Journal of Research in Interdisciplinary Studies, 2025)
The rapid increase in vehicular traffic on highways has led to rising concerns regarding congestion, delays, and road safety, especially at intersections. Rotary intersections, which allow vehicles to circulate around a central island, provide an efficient solution to reduce conflicts, improve traffic flow, and enhance pedestrian safety. This study presents a comparative analysis between manual and software-aided methods for designing rotary intersections, with a specific focus on the application of AutoCAD Civil 3D software. The primary objective is to assess the efficiency, accuracy, and cost-effectiveness of using AutoCAD Civil 3D compared to traditional manual design approaches. The selected site for this study is the rotary intersection at Santoshi Nagar Chowk in Raipur. The design was first developed using manual methods based on IRC standards and then replicated using AutoCAD Civil 3D to evaluate differences in time consumption, design accuracy, earthwork estimation, and visualization capabilities. The results demonstrate that AutoCAD Civil 3D significantly improves design efficiency by automating complex tasks such as corridor modeling, surface creation, and earthwork quantity calculation. It also offers enhanced 3D visualization, dynamic editing capabilities, and better documentation. While manual methods are still relevant for basic design understanding and calculations, they are more time-consuming and prone to human error. This comparative study concludes that software-aided design using Civil 3D not only saves time and resources but also ensures greater precision, making it a preferred tool for modern transportation engineering projects.